Transgender Health: New Zealand’s Innovative Statistical Standard for Gender Identity - Pega, Frank (Am J Public Health, 2017)
The implementation of the New Zealand government’s recently developed statistical standard for gender identity has led to, and will stimulate further, collection of gender identity data in administrative records, population surveys, and perhaps the census. This will provide important information about the demographics, health service use, and health outcomes of transgender populations to allow evidence-based policy development and service planning. However, the standard does not promote the two-question method, risking misclassification and undercounts; does promote the use of the ambiguous response category “gender diverse” in standard questions; and is not intersex inclusive. Nevertheless, the statistical standard provides a first model for other countries and international organizations, including United Nations agencies, interested in policy tools for improving transgender people’s health.